2020
DOI: 10.1073/pnas.2008410117
|View full text |Cite|
|
Sign up to set email alerts
|

BCG vaccine protection from severe coronavirus disease 2019 (COVID-19)

Abstract: A series of epidemiological explorations has suggested a negative association between national bacillus Calmette–Guérin (BCG) vaccination policy and the prevalence and mortality of coronavirus disease 2019 (COVID-19). However, these comparisons are difficult to validate due to broad differences between countries such as socioeconomic status, demographic structure, rural vs. urban settings, time of arrival of the pandemic, number of diagnostic tests and criteria for testing, and national control strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
452
4
13

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 403 publications
(517 citation statements)
references
References 34 publications
23
452
4
13
Order By: Relevance
“…It has merit theoretically but is di cult to be established due to BCG vaccine's long preparatory period and known poor e cacy in adult population. 12 The present work probably establishes a direct correlation between Mtb induced Th1 immunity and protection against Covid-19. The restoration of Th1/Th2 imbalance may be a more natural strategy to ght against Covid-19.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…It has merit theoretically but is di cult to be established due to BCG vaccine's long preparatory period and known poor e cacy in adult population. 12 The present work probably establishes a direct correlation between Mtb induced Th1 immunity and protection against Covid-19. The restoration of Th1/Th2 imbalance may be a more natural strategy to ght against Covid-19.…”
Section: Discussionsupporting
confidence: 63%
“…Similar observations were made authors who reported strong correlation between the BCG index, an estimation of the degree of universal BCG vaccination deployment in a country, and COVID-19 mortality in different socially similar European countries (r2 = 0.88; P = 8 × 10−7). 12 COVID-19−related deaths are signi cantly higher in countries with higher quality of life, contradicting the expectation of lower rates of mortality in countries with improved health care systems. 12 Though India has become the third highest country with maximum number of Covid-19 patients, it continues to shows signi cantly lower prevalence of the disease, both in terms of disease and deaths per million population in comparison to other top 15-20 countries .22 Natural course for most of Covid-19 patients in Th1 predominant population may be to remain asymptomatic or minimally symptomatic which is re ected in the epidemiological reports from India and other similar countries like south America etc.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…There is strong epidemiological evidence that BCG vaccination in infants has a broad protective effect and reduces the overall mortality from respiratory infections not related to tuberculosis (21)(22)(23), and there are ongoing clinical studies to establish if the BCG vaccine also protects from severe COVID19 (24,25). Furthermore, there is growing epidemiological evidence of reduced COVID19 mortality (26) and improved outcomes (27) in countries with strong BCG vaccination programs. However, little is known about the mechanism to establish and maintain trained immunity.…”
Section: Antibodies To Recombinant Dblox Detected a Single Band Undermentioning
confidence: 99%